1997
DOI: 10.1557/jmr.1997.0066
|View full text |Cite
|
Sign up to set email alerts
|

Comments on the effects of solution precursor characteristics and thermal processing conditions on the crystallization behavior of sol-gel derived lead zirconate titanate thin films

Abstract: Lead zirconate titanate (PZT 40/60) thin films were fabricated on electroded silicon wafers using chemical solution deposition. Two different chelating agents, acetic acid and acetylacetone, were used in the synthesis of the precursor solutions. The microstructure of the acetylacetone-derived film was characterized by nucleation at the platinum electrode and a columnar growth morphology (˜100−200 nm lateral grain size). In contrast, the acetic acid-derived film was characterized by both columnar grains nucleat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(75 citation statements)
references
References 20 publications
2
71
0
2
Order By: Relevance
“…The very small band at 2300 cm −1 is due to adsorbed or atmospheric CO 2 [2,21]. The characteristic small bands at 1716 and 1338 cm −1 are assigned to both asymmetric and symmetric C-O, respectively [2,19,21].…”
Section: Fourier Transform Infrared Spectroscopy (Ftir) Analysismentioning
confidence: 96%
See 1 more Smart Citation
“…The very small band at 2300 cm −1 is due to adsorbed or atmospheric CO 2 [2,21]. The characteristic small bands at 1716 and 1338 cm −1 are assigned to both asymmetric and symmetric C-O, respectively [2,19,21].…”
Section: Fourier Transform Infrared Spectroscopy (Ftir) Analysismentioning
confidence: 96%
“…The characteristic small bands at 1716 and 1338 cm −1 are assigned to both asymmetric and symmetric C-O, respectively [2,19,21]. The C-O bands region is an indicative of the presence of organic residues due to acetylacetone species [21].…”
Section: Fourier Transform Infrared Spectroscopy (Ftir) Analysismentioning
confidence: 98%
“…La existencia de esa fase coebica de Pt 3 Ti inducir'a la nucleaci-n de cristales de perovskita orientados en <111>, siempre que esta primera capa de Pb 0.76 Ca 0.24 TiO 3 fuese lo suficientemente fina como para que la nucleaci-n fuese heterogŽnea (3). Efectivamente, como se ha indicado en la parte experimental para la obtenci-n de l ‡minas con espesores de ~300 nm, se han depositado y cristalizado cuatro monocapas de ferroelŽctrico, lo que indica que el espesor promedio de cada monocapa es dẽ 75 nm, espesor suficientemente peque-o como para que la perovskita nuclee mayoritariamente de forma heterogŽnea (8). El dep-sito de capas tan finas tambiŽn disminuye el grado de tensiones desarrolladas en las l ‡minas (9), haciendo posible que en este caso sea peque-a la contribuci-n de este factor al grado de orientaci-n de la pel'cula.…”
Section: Resultados Y Discusiînunclassified
“…17 In addition, in chemical solution derived films, the pathway from an amorphous to a final crystalline state passes through an intermediate phase whose structure and stoichiometry is often different than the desired final phase. [18][19][20] Theoretical work has recently revealed that inhomogeneities and concentration gradients may act as an effective internal field that smears out the phase transition 21 and reduces the permittivity. The low temperatures used in thin film annealing coupled with point defect formation may significantly affect the local structure and properties of the final crystalline phase.response in PST showed that the small film permittivity is truly a property of the film, and not the result of a surface passive layer.…”
Section: Introductionmentioning
confidence: 99%